Investigating Pollen and Gene Flow of WYMV-Resistant Transgenic Wheat N12-1 Using a Dwarf Male-Sterile Line as the Pollen Receptor. - Shanshan Dong; Yan Liu; Cigang Yu; Zhenhua Zhang; Ming Chen; Changyong Wang (PLoS ONE)
Pollen-mediated gene flow (PMGF) is the main mode of transgene flow in flowering plants. The study of pollen and gene flow of transgenic wheat can help to establish the corresponding strategy for preventing transgene escape and contamination between compatible genotypes in wheat. To investigate the pollen dispersal and gene flow frequency in various directions and distances around the pollen source and detect the association between frequency of transgene flow and pollen density from transgenic wheat, a concentric circle design was adopted to conduct a field experiment using transgenic wheat with resistance to wheat yellow mosaic virus (WYMV) as the pollen donor and dwarf male-sterile wheat as the pollen receptor. The results showed that the pollen and gene flow of transgenic wheat varied significantly among the different compass sectors. A higher pollen density and gene flow frequency was observed in the downwind SW and W sectors, with average frequencies of transgene flow of 26.37 and 23.69% respectively. The pollen and gene flow of transgenic wheat declined dramatically with increasing distance from its source. Most of the pollen grains concentrated within 5 m and only a few pollen grains were detected beyond 30 m. The percentage of transgene flow was the highest where adjacent to the pollen source, with an average of 48.24% for all eight compass directions at 0 m distance. Transgene flow was reduced to 50% and 95% between 1.61 to 3.15 m, and 10.71 to 20.93 m, respectively. Our results suggest that climate conditions, especially wind direction, may significantly affect pollen dispersal and gene flow of wheat. The isolation-by-distance model is one of the most effective methods for achieving stringent transgene confinement in wheat. The frequency of transgene flow is directly correlated with the relative density of GM pollen grains in air currents, and pollen competition may be a major factor influencing transgene flow.